Single-oscillator model and determination of optical constants of some optical thin film materials - Yakuphanoğlu, Fahrettin; Cukurovali, A; Yilmaz, I (Elsevier, 2004)
The optical properties of some optical thin film materials have been investigated by means of the optical transmittance and reflectance spectra. The dispersion of the refractive index is discussed in terms of the Wemple-DiDomenico single oscillator model. The optical band gap values were calculated for Taue model and Wemple-Didomenico model. The optical band gaps which turned out to depend significantly on the metal coordination were calculated in terms of Taue method and Wemple-Didomenico model. The E-opt(WD) values obtained from Wemple-Didomenico model are in agreement with those determined from the Taue model. The type of optical transition responsible for optical absorption is indirect transition with an energy gap of 2.12-2.39 eV. The dispersion energies E-d of the thin films are in the range of 29.69-14.32 eV. The real and imaginary parts of the dielectric constant of the films were determined. The real and imaginary parts follow the same pattern and it is seen that the values of real part are higher than imaginary parts. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: optical materials; dispersion of refractive index; optical band gap